PENGARUH PRODUK, TEMPAT, PROMOSI SERTA KEPERCAYAAN TERHADAP LOYALITAS PASIEN DIMEDIASI KEPUASAN DI PUSKESMAS TAMBAK WEDI - Retno Nur Handayani; Basuki Rachmat (Universitas PGRI Adi Buana, 2025)
This study aims to examine the influence of product, place, promotion, and trust on patient loyalty, mediated by patient satisfaction at Puskesmas Tambak Wedi. Utilizing a quantitative approach with a cross-sectional design, data was collected from patients who had visited the facility at least three times in the last year. The study found that product quality, location, promotion, and trust significantly affected patient satisfaction. Additionally, patient satisfaction had a positive and significant impact on patient loyalty. The findings highlight the importance of strategic service quality improvements, including service offerings, effective communication, and trustworthy interactions with medical staff, to enhance patient loyalty in primary healthcare settings. The results contribute to understanding the complex dynamics of healthcare service management and provide practical recommendations for enhancing patient loyalty in community healthcare centers.